Bilateral deficit and EMG activity during explosive lower limb contractions against different overloads - Rejc, E.; Lazzer, S.; Antonutto, G.; Isola, M.; Di Prampero, P. E. (European Journal of Applied Physiology, 2010)
We investigated whether bilateral deficit (BLD): (1) is observed during explosive lower limb contractions; (2) can be attributed to a reduction of neural drive and/or (3) to a different muscle coordination, and/or (4) to changes of the muscle force-velocity (F-v) relationship. Ten volunteers performed maximal explosive efforts of ~450 ms on a sledge ergometer, with both lower limbs (BL), with the right and left limb separately (ML), against different overloads. Peak-force (F, N), peak-power (w, W), sledge peak-velocity (v, m/s) and electromyography (EMG) of vastus lateralis (VL), rectus femoris (RF), biceps femoris (BF) and gastrocnemius medialis (GM) were recorded. Average values over the six overloads of F and w, developed by right or left limb during BL, were significantly lower (883 ± 200 and 918 ± 141 N; 1089 ± 407 and 1099 ± 325 W) than those developed during ML contractions (1285 ± 177 and 1306 ± 147 N; 1536 ± 408 and 1497 ± 392 W). VL and RF iEMGs were lower in BL than in ML (74 ± 28 vs. 91 ± 21% MVC and 39 ± 21 vs. 56 ± 28% MVC). The coordination among the four muscles, as determined from an analysis of the time course of iEMG, expressed as percentage of that attained at the end of the push, was poorer in BL, as compared to ML. BL F-v curves were different as compared to the ML ones, the force and power developed, at a given v, being significantly larger in ML. It is concluded that BLD occurs also during explosive pushes with the lower limbs, and that it is mainly due to different muscle coordination.